State of the art on pre-tensioning steel straps confinement: literature review - Ma, Chau-Khun; Awang, Abdullah Zawawi; Omar, Wahid; Sarbini, Noor Nabilah; Shahidan, Shahiron (Construction Research Institute of Malaysia (CREAM), 2018)
This paper presents the state-of-the-art of the current research development on pre-tensioning steel straps confinement. Critical review was conducted based on careful selection of references to provide in-depth overview in the development of this confining technique. The paper was started with highlighting the features of such confining technique, then an extensive description of the connection clip systems was presented. The experimental and numerical investigations performed on steel-strapped concrete structures were discussed at length in the paper. The potential usage of pre-tensioning steel straps confinement in increasing the bond properties of confined concrete and as a repairing technique of damaged concrete were also covered in this paper.